Comparative response analysis of conventional and innovative seismic protection strategies. - Bruno, S. (Earthquake engineering & structural dynamics.)
The paper presents a numerical investigation aimed at evaluating the improvements achievable through devices for passive seismic protection of buildings based on the use of shape memory alloys (SMA) in place of conventional steel or rubber devices. To get some generality in the results, different resisting reinforced concrete plane frames were analysed, either protected or not. 'New' and 'existing' buildings were considered depending on whether seismic provisions are adopted in the building design or not. Base isolation and energy dissipation were equally addressed for both conventional and innovative SMA based devices. Fragility analyses were performed using specific damage measures to account for comparisons among different damage types; the results were then used to estimate quantitatively the effectiveness of the various protection systems. More specifically, the assessment involved a direct comparison of the damage reduction provided by each protection system with respect to the severe degradation experienced by the corresponding non protected frame. Structural damage, non-structural damage and damage to contents were used on purpose and included in a subsequent phase of cost analysis to evaluate the expected gains also in terms of economic benefits and life loss prevention. The results indicate that base isolation, when applicable, provides higher degrees of safety than energy dissipation does; moreover, the use of SMA based devices generally brings about better performances, also in consideration of the reduced functional and maintenance requirements.